2020
DOI: 10.1186/s12889-020-09216-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Management of Childhood Illnesses implementation-related factors at 18 Colombian cities

Abstract: Background Integrated Management of Childhood Illnesses (IMCI) is a strategy developed by the World Health Organization (WHO) and UNICEF in 1992. It was deployed as an integrated approach to improve children’s health in the world. This strategy is divided into three components: organizational, clinical, and communitarian. If the Integrated Management of Childhood Illnesses implementation-related factors in low- and middle-income countries are known, the likelihood of decreasing infant morbidity an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(15 reference statements)
0
6
0
1
Order By: Relevance
“…Estudo na Etiópia demonstrou que os problemas mais comuns encontrados na implementação do AIDPI estão relacionados à falta de treinamento, de medicamentos, suprimentos essenciais e principalmente de supervisão e visita de acompanhamento (20) . Outro estudo quantitativo, realizado na Colômbia, revelou que a assistência realizada para as crianças menores de cinco anos continua incompleta, pois não apresenta o mínimo necessário para implementação adequada do AIDPI no país (21) .…”
Section: Discussionunclassified
“…Estudo na Etiópia demonstrou que os problemas mais comuns encontrados na implementação do AIDPI estão relacionados à falta de treinamento, de medicamentos, suprimentos essenciais e principalmente de supervisão e visita de acompanhamento (20) . Outro estudo quantitativo, realizado na Colômbia, revelou que a assistência realizada para as crianças menores de cinco anos continua incompleta, pois não apresenta o mínimo necessário para implementação adequada do AIDPI no país (21) .…”
Section: Discussionunclassified
“…WHO recommends one of the treatments for sick toddlers in developing countries through the Integrated Management of Childhood Illness (IMCI), which is an integrated approach to the management of sick toddlers with a focus on the health of children aged 0-5. years (toddlers) as a whole, in this IMCI-based management one of the components is improving family and community practices in-home care and efforts to seek help for sick toddlers (impact increasing community empowerment in health services) (García Sierra & Ocampo Cañas, 2020) (Kementrian kesehatan Republik Indonesia, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A nurse is someone who is highly educated in nursing and carries out nursing activities based on nursing science by providing care to individuals, families, groups, or communities. Family empowerment interventions in sick children based on scientific evidence can be used as the basis for interventions for nurses in the care of sick toddlers (García Sierra & Ocampo Cañas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the overuse of antibiotics obtained from unqualified providers and drug shops in Bangladesh, and 80-90% of drug shops and medicine vendors operate without a license [8,13,19,28]. Additionally, the adequate supervision and inspection of drug outlets are complicated by the limited availability of drug inspectors (i.e., one drug inspector supervises 2236 pharmacy shops) [6]. Initiatives, such as the 'model pharmacy', which accredit pharmacies for meeting high standards of practice, may help to reduce over the counter purchases of antibiotics [29].…”
Section: Discussionmentioning
confidence: 99%
“…These illnesses include acute respiratory infections (ARIs), accounting for 50-75% of febrile presentations at outpatient clinics, and gastroenteritis, accounting for 10-25% of febrile illnesses. Clinical practice guidelines (CPGs), such as the Integrated Management of Childhood Illness (IMCI), aim to standardise the symptomatic management of fever in children [6]. These guidelines promote the rational use of antimicrobials by recommending antibiotics be exclusively prescribed to children who are presumed to have a disease that can be treated using antibiotics, based on World Health Organisation (WHO) recommendations [7].…”
Section: Introductionmentioning
confidence: 99%